Can We Simulate the Work Environment? How we Prepare Students for Practice. Issue 1 (1st January 2023) - Moody, Iain; Huby-Ayers, Katherine; Taylor, Sarah
Abstract : This paper describes the joint development of a simulation for social work students by academics and practitioners. The simulation aimed to support students to have a broader understanding of the role of a social worker in the Local Authority teams. The simulation looked to facilitate students undertaking the role of the social worker from initial referral to final written assessment.